The role of nutrition in lipid disorders treatment - Orlicz-Szczęsna, Grażyna; Szymańska, Monika; Kucharska, Katarzyna (Current Problems of Psychiatry, 2011)
Prevention and treatment of lipid disorders are still challenges to modern medicine. There is a great deal of evidence that lipid disorders increase cardiovascular risk. The primary target of cholesterol-lowering treatment is the reduction of LDL cholesterol as a particular atherogenic lipoprotein. Many clinical studies confirmed a close relationship between the LDL cholesterol lowering and the cardiovascular risk reduction. The elevated plasma triglyceryde and reduced HDL cholesterol concentration also increase that risk.In the face of constantly increasing costs of pharmacotherapy of lipid disorders in primary and secondary prevention of cardiovascular diseases, maximum effort should be made to change the lifestyle, which mainly includes the modification of eating habits. As modifiable risk factors, they are the base of lipid disorders treatment. They constitute a necessary addition to and increase the effectiveness of pharmacotherapy and, in some cases, they reduce the need for drug therapy. Despite the growing awareness of the society, its knowledge of a healthy nutrition still seems to be insufficient. More emphasis should be put on education of people with multiple risk factors of cardiovascular diseases.This work focuses on the influence of nutrition on the lipid profile. The interaction between specific nutrients and the concentration of a particular group of lipids have been discussed. The special role of saturated fatty acids, as the component of a diet which elevates the LDL cholesterol the most, has been taken into consideration. The beneficial influence of plant stanols and sterols, soy protein and viscous fiber has been emphasized.